Impact of morphine dependency and detoxification by methadone on male's rat reproductive system - Mahnaz Ghowsi; Namdar Yousofvand (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2015)
Background: One of the problems that addicts suffer from is decreased libido. Erectile dysfunction has been reported in men using opioids for treatment of heroin addiction. Objective: The study was performed to investigate the effects of morphine and detoxification with methadone as causes of sexual dysfunction in addiction. Methods and Methods: A total of 40 adult male rats (Wistar) were used. Animals were divided in to 4 groups. Control groups received saline for 30 days. Other 2 groups received 10 mg/kg morphine on day 1 and the morphine doses increased daily by 2 mg/kg increments per day until in day 30 a maximum of 68 mg/kg twice daily was achieved. Withdrawal syndrome sings were evaluated. At the end of period, one group of 2 morphine dependent groups was treated with methadone during 14 days. Animals in group 4 (saline solution+ methadone) received saline for 30 consecutive days and then detoxified with methadone during 14 days. Partial weights of seminal vesicles, testes, prostates, seminal vesicles content, concentrations of luteinizing hormone, follicle stimulating hormone, and testosterone in serum were determined. Results: In the dependent group serum levels of testosterone (p<0.001), folicle stimulating hormone (p=0.0097) and luteinizing hormone (p=0.0031) as well as the weights of testes (p=0.0051), partial weights of prostates, seminal vesicles and seminal vesicles contents (p<0.001) were reduced as compared with control group. In the morphine dependent animals detoxified with methadone, testosterone concentrations and seminal vesicles contents remained lower than levels in the control group (p<0.001). Conclusion: The results suggest that morphine dependence may impair the reproductive function in male rats.